Emotional and Cognitive Drivers of Repurchase Intention in A Family-Owned Bakery Business - Simamora, Damerina; Fernando, Agus (Faculty of Business, President University, 2025)
Introduction/Main Objectives: This study explores the factors influencing repurchase intention in a family-owned bakery, Roti Ganda, by examining how food quality, price perception, brand trust, and brand love affect customer satisfaction and loyalty. In the context of Indonesia’s growing SME sector, understanding the emotional and rational drivers of customer behavior is crucial for sustaining competitive advantage. Background Problems: This study addresses the decline in repeat purchases at Roti Ganda by analyzing how customer perceptions and emotions shape repurchase intentions. Novelty: While prior research has independently examined rational or emotional factors, this study uniquely integrates both within a single model, highlighting customer satisfaction’s mediating role. Research Methods: A quantitative, cross-sectional survey was conducted with 414 Roti Ganda customers using validated Likert-scale instruments. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test seven hypotheses. Finding/Results: Results show that food quality, price perception, and brand love significantly influence customer satisfaction and repurchase intention. Surprisingly, brand trust did not have a direct effect. Customer satisfaction fully mediates the relationship between product and emotional attributes and loyalty. Conclusion: Family businesses should prioritize product quality and emotional connection to enhance loyalty. Brand trust alone is insufficient without operational consistency. This study provides theoretical insight into emotional–cognitive integration and practical strategies for family-run food enterprises.